4
$\begingroup$

i've been stuck on this question too long

$x = \sec A + \tan A$

show $x + \frac{1}{x} = 2\cdot \sec A$

I've been using $\tan^2 \theta + 1 = \sec^2 \theta$

and $\tan\theta = \frac{\sin \theta}{\cos\theta}$

help would be much appreciated


$x=\sec A +\tan A = \frac{1}{\cos A}+\frac{\sin A}{\cos A}=\frac{1+\sin A}{\cos A}$

$\endgroup$
6
$\begingroup$

$$ x=\sec A + \tan A= \frac{1}{\cos A}+\frac{\sin A}{\cos A}=\frac{1+\sin A}{\cos A} $$

so we have:

$$ x+\frac{1}{x}= \frac{1+\sin A}{\cos A}+\frac{\cos A}{1+\sin A}=\frac{1+\sin^2 A+2\sin A+\cos^2 A}{(\cos A)(1+ \sin A)}= $$ $$ =\frac{2(1+\sin A)}{(\cos A)(1+ \sin A)}=\frac{2}{\cos A} $$

$\endgroup$
4
$\begingroup$

Because $$x+\frac{1}{x}=\frac{1+\sin{A}}{\cos{A}}+\frac{\cos{A}}{1+\sin{A}}=$$ $$=\frac{(1+\sin{A})^2}{\cos{A}(1+\sin{A})}+\frac{\cos^2{A}}{\cos{A}(1+\sin{A})}=\frac{(1+\sin{A})^2+\cos^2A}{\cos{A}(1+\sin{A})}=$$ $$=\frac{1+2\sin{A}+\sin^2A+\cos^2A}{\cos{A}(1+\sin{A})}=\frac{1+2\sin{A}+1}{\cos{A}(1+\sin{A})}=$$ $$=\frac{2+2\sin{A}}{\cos{A}(1+\sin{A})}=\frac{2}{\cos{A}}=2\sec{A}.$$

$\endgroup$
  • $\begingroup$ How did you from the first step to the second? $\endgroup$ – Inquirer Feb 17 '18 at 16:48
  • $\begingroup$ Because $(1+\sin{A})^2+\cos^2A=1+2\sin{A}+\sin^2A+\cos^2A=2+2\sin{A}$. $\endgroup$ – Michael Rozenberg Feb 17 '18 at 16:50
  • $\begingroup$ i don't see how you applied this to the question, please explain. $\endgroup$ – Inquirer Feb 17 '18 at 16:54
  • $\begingroup$ Yes, I get it now. Thanks $\endgroup$ – Inquirer Feb 17 '18 at 17:05
3
$\begingroup$

x=secA + tanA

1/x= 1/(secA + tanA). = (secA - tanA)/(secA-tanA)(secA+tanA) =(secA - tanA)/{(secA)^2 - (tanA)^2} = secA - tanA

Therefore

x+ 1/x = (secA + tanA)+(secA - tanA) = 2SecA

$\endgroup$
1
$\begingroup$

Enough to show:

$$\cos{A}\left( x + \frac{1}{x}\right) = 2$$

$$\cos{A} \cdot x + \frac{\cos{A}}{x} = 1 +\sin{A} + \frac{\cos^2{A}}{1 +\sin{A}} = 1 +\sin{A} + \frac{1-\sin^2{A}}{1 +\sin{A}} = 2 $$

$\endgroup$
0
$\begingroup$

we get $$x+\frac{1}{x}={\frac { \left( \sec \left( A \right) \right) ^{2}+2\,\sec \left( A \right) \tan \left( A \right) + \left( \tan \left( A \right) \right) ^{2}+1}{\sec \left( A \right) +\tan \left( A \right) }} $$ can you simplify this term? the numerator simplifies to $$-\frac{2}{\sin(A)-1}$$ and $$\sec(A)+\tan(A)=\frac{\sin(A)+1}{\cos(A)}$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.